Two new species of Terebrasabella (Annelida: Sabellidae: Sabellinae) from Australia - Murray, Anna; Rouse, Greg W. (Zootaxa, 2007)
Two new species of Terebrasabella Fitzhugh & Rouse, 1999 are described from eastern Australia. Terebrasabella hutchingsae sp. nov., was found from preserved coral rock debris collected in 1977 on the outer Barrier Reef near Lizard Island, Queensland. Terebrasabella fitzhughi sp. nov., was found alive in burrows in and among spirorbin serpulid tubes on intertidal rocks in Tasmania in 1996. Both species were found in mucoid tubes, and brood their young in a manner similar to the only other described species of Terebrasabella, T. heterouncinata Fitzhugh & Rouse, 1999. Terebrasabella hutchingsae sp. nov., is exceptional as it possesses a type of thoracic neurochaetal uncinus different from the other two species, and which is similar to the notochaetal acicular “palmate hook” seen in Caobangia. Descriptions of both species are given, and the diagnosis for Terebrasabella is emended. Larval and chaetal morphology and relationships among of the three known Terebrasabella spp. are discussed.